1990
DOI: 10.1111/j.1365-3040.1990.tb01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Stable carbon isotope fractionation by marine phytoplankton during photosynthesis

Abstract: Abstract. In the marine environment, the range of values of carbon isotope fractionation between particulate tissue of phytoplankton and inorganic carbon can be more than 20‰ (− 35‰ < δ13C < − 14‰). This review considers the influence of seawater temperature, lipid content of phytoplanktonic cells, kinetic fractionation, and carbon pathway on δ13C values observed at sea. In order to study the contribution of carboxylases (RUBISCO and the β‐carboxylases phosphoenolpyruvate carboxylase, phosphoenoplpyruvate carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(68 citation statements)
references
References 57 publications
5
61
2
Order By: Relevance
“…Carbon isotopic fractionations among organic compound classes in phytoplankton has been well-Ž recognized Abelson and Hoering, 1961;De Niro and Epstein, 1977;Descolas-Gros and Fontugne, . 1990;Fischer, 1991 .…”
Section: Comparison Of D 13 C Signatures In Plankton and Sediments Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon isotopic fractionations among organic compound classes in phytoplankton has been well-Ž recognized Abelson and Hoering, 1961;De Niro and Epstein, 1977;Descolas-Gros and Fontugne, . 1990;Fischer, 1991 .…”
Section: Comparison Of D 13 C Signatures In Plankton and Sediments Ofmentioning
confidence: 99%
“…During photosynthesis, phyto-Ž . plankton fix dissolved inorganic C DIC in the surface water into organic biomass C by enzymatic Ž carboxylation reactions Descolas-Gros and Fontugne, 1990;Fogel and Cifuentes, 1993;Goer-. icke et al, 1993 .…”
Section: Comparison Of D 13 C Signatures In Plankton and Sediments Ofmentioning
confidence: 99%
“…Biochemical and biophysical considerations have recently been very thoroughly and helpfully reviewed by Goericke et al (1993), and other investigators have interpreted variations of ap observed in natural systems in terms of varying levels of enzymatic activity and pathways of carbon fixation (Descolas-Gros et al, 1990;Fontugne et al, 1991), growth rate and cell size (Takahashi et al, 1991;Fry and Wainright, 1992), and speciesrelated physiological differences (Falkowski, 1991). Fogel et al (1992) have called upon many of these factors to explain observed variations in 6p in a seasonal study of the complex Chesapeake estuary.…”
Section: Co 2 Paleobarometrymentioning
confidence: 99%
“…Primary production from Nfixation is a major source in this ocean region, at times resulting in δ 15 N of fresh POM near 0‰ (Dore et al 2002;Karl 1999). At the same time, additional proteinaceous material should lead to both lower C/N ratios and heavier δ 13 C, since amino acids are generally 13 C enriched relative to other biochemical components (e.g., Degens et al, 1968;Descolasgros and Fontugne 1990). Thus, this explanation is consistent with both expected δ 13 C of different biochemical classes, local sources, and finally also with "size-reactivity" continuum ideas (Amon and Benner 1994), which would predict larger material to be less degraded.…”
mentioning
confidence: 99%